How do youth innovate to make agriculture gainful? Challenges and youth entrepreneurs in mid-western Uganda - Loga, Dorcas Elizabeth; Kibwika, Paul; Kyazze, Florence Birungi (International Journal of Agricultural Research, Innovation and Technology, 2022)
The global population is expected to increase to 9 billion by 2050, with the youth accounting for 14 per cent of this total. While the world's youth population is expected to grow, employment and entrepreneurial opportunities for youth, particularly those living in low and middle-income countries remain limited, poorly remunerated and of poor quality. The Ugandan population, in particular, is largely comprised of a high youthful population with 78 percent below the age of thirty. Evidence reveals that youth engagement in agriculture is declining, and in recognition of the agricultural sector's potential to serve as a source of livelihood opportunities, this study assesses the factors impeding youth engagement and the drivers of innovation among the youth engaged in agricultural enterprises in Mid-Western Uganda. Anchoring in the Agricultural Innovation System (AIS), cross-sectional survey and case study research designs were employed to establish the innovativeness of youth, and the factors impeding engagement in agricultural enterprises from the youth's perspective. A pairwise ranking of the factors was also independently done. The findings reveal that the significant factors restraining youth engagement in agricultural enterprises as enhancing soil productivity, access to relevant technical knowledge and information, and access to land for production. The major innovations for successful youth engagement in agriculture are irrigation to reduce risks of dependence on rain, mechanization to reduce labour struggle, and market linkages. The case studies' innovation index portrays a high potential of innovativeness of youth to revolutionize and make agriculture gainful and attractive to the youth. Int. J. Agril. Res. Innov. Tech. 12(1): 39-44, June 2022